Influence of gender, education, age group and time in the company on the adoption of new technologies and their impact on continuous improvement - Dinis-Carvalho, José (2022)
Continuous Improvement (CI) is a principle being adopted in many organizations around the world. It is present in relevant excellence models such as the Toyota Way, Shingo Model, and Lean Thinking. CI was implemented some years ago in a Public Company (Lipor) based in Porto, dedicated to municipal waste treatment, but the Covid-19 pandemic created some important challenges. The forced adoption of new technologies associated with I4.0 required important changes in the existing CI routines. This paper aims to assess the influence of gender, education, age group, and time in the company on adopting new technologies used in their IC routines. This study, based on employees' perceptions through questionnaires, shows that the CI system had, in general, a positive impact on their work and overall performance. Regarding the effect of forced teleworking caused by COVID-19 on office workers, this study shows that age, gender, education, and years in the company have an impact on the effective adoption of new technologies associated with digital transformation and Industry 4.0. The study also shows that those technologies effectively allow routines and culture of CI to be maintained when workers are forced to work remotely.